Regulation of IL (Interleukin)-33 Production in Endothelial Cells via Kinase Activation and Fas/CD95 Upregulation. Issue 11 (November 2020) - Duez, Catherine; Gross, Barbara; Marquillies, Philippe; Ledroit, Valérie; Ryffel, Bernhard; Glineur, Corine
Abstract : Objective: The occurrence of new blood vessel formation in the lungs of asthmatic patients suggests a critical role for airway endothelial cells (ECs) in the disease. IL-33 (Interleukin-33)—a cytokine abundantly expressed in human lung ECs—recently emerged as a key factor in the development of allergic diseases, including asthma. In the present study, we evaluated whether mouse and human ECs exposed to the common Dermatophagoides farinae allergen produce IL-33 and characterized the activated signaling pathways. Approach and Results: Mouse primary lung ECs were exposed in vitro to D farinae extract or rmIL-33 (recombinant murine IL-33). Both D farinae and rmIL-33 induced Il-33 transcription without increasing the IL-33 production and upregulated the expression of its receptor, as well as genes involved in angiogenesis and the regulation of immune responses. In particular, D farinae and rmIL-33 upregulated Fas/Cd95 transcript level, yet without promoting apoptosis. Inhibition of caspases involved in the Fas signaling pathway, increased IL-33 protein level in ECs, suggesting that Fas may decrease IL-33 level through caspase-8-dependent mechanisms. Our data also showed that the NF-κB (nuclear factor-κB), PI3K/Akt, and Wnt/β-catenin pathways regulate Il-33 transcription in both mouse and human primary ECs. Conclusions: Herein, we described a new mechanism involved in the control of IL-33 production in lung ECs exposed to allergens. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.